Pseudrotasfer microincubator gen. et spec. nov., a brooding cucumariid holothurian (Echinodermata: Holothuroidea: Dendrochirotida) from the Burdwood Bank (south-western Atlantic Ocean) - Bohn, Jens Michael (Zootaxa, 2007)
A new brooding cucumariid holothurian, Pseudrotasfer microincubator gen. et sp. nov. has been discovered in samples taken by the LAMPOS expedition with FS “Polarstern” at Burdwood Bank in the south-western Atlantic Ocean. This species is characterised by peculiar wheel-like baskets in its outer body wall and a deeper layer of simple large perforated plates, that require the establishment of a new genus. The new genus and species are characterised, and a description is provided of its external and internal morphology, including a SEM study of its ossicles.